Summary of the 2015 University of Michigan Sport Concussion Summit - Steven P Broglio; Grant Baldwin; Rudy J Castellani; Sara PD Chrisman; Stefan Duma; Brian Hainline; Joanne C Gerstner; Kevin Guskiewicz; Jeffrey Kutcher; Adria Lamba; Michael McCrea; Steven Pachman; et al. (Concussion, 2016)
Discussions surrounding concussion have made their way into the public sphere over the previous decade with media attention and coverage of the injury fueling public debate. These conversations hav...